Human Rights of Indigenous Small-Numbered Peoples in Russia: Recent Developments - Zmyvalova , Ekaterina (Arctic Review on Law and Politics, 2020)
In Russia, there exist legal norms providing for the protection of indigenous small-numbered peoples’ rights. Yet, indigenous small-numbered peoples face multiple challenges when it comes to the implementation of their rights. After a brief presentation of the Russian legislation on the rights of indigenous small-numbered peoples, peculiarities of the Russian legal system and impediments to the legal provisions regulating the status of indigenous small-numbered peoples, this article addresses several issues related to the implementation of indigenous small-numbered peoples’ rights in Russia today. One of the core issues is the attribution of individual members of indigenous communities to indigenous small-numbered peoples. Such an attribution is still challenging despite the newly adopted amendments to the 30 April 1999 Federal Law N 82-FL: ‘On Guarantees of the Rights of Indigenous Small-Numbered Peoples of the Russian Federation’. Another issue is application of the notion ‘foreign agent’ to individuals and non-commercial organizations. Still another issue is the State’s pressure on independent indigenous organizations. The final challenge is the possible impact of amendments to the Constitution approved by popular vote in July 2020 on the rights of indigenous small-numbered peoples.